2007
DOI: 10.1002/jbm.a.31386
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel bioactive glasses support both osteoblast and osteoclast formation from human bone marrow cells

Abstract: We have examined the ability of bioactive sol-gel glass ceramics to support both osteoblast and osteoclast differentiation from human bone marrow cells (HBMC). Nucleated cells from human bone marrow were cultured on tissue culture plastic and on two sol-gel coatings: A2 glass-ceramic containing 54 mol % CaO/40 mol % SiO(2) and S2 glass-ceramic containing 16 mol % CaO/80 mol % SiO(2). Osteoblast differentiation was followed by measuring alkaline phosphatase (ALP) activity, mRNA levels for ALP, osteopontin, RANK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…Our earlier studies reported the production, physico-chemical, and biological properties of gel-derived bioactive glasses of the CaO–P 2 O 5 –SiO 2 system 19,27. We showed that CaO:SiO 2 ratio in these glasses influenced their physical and chemical properties and affected the growth and differentiation of bone marrow-derived cells 6,17,20. Our data further indicate that incorporation of these gel-derived glasses into a HA matrix enhanced growth and osteogenic differentiation of human mesenchymal stem cells (MSC) 5.…”
Section: Introductionmentioning
confidence: 57%
“…Our earlier studies reported the production, physico-chemical, and biological properties of gel-derived bioactive glasses of the CaO–P 2 O 5 –SiO 2 system 19,27. We showed that CaO:SiO 2 ratio in these glasses influenced their physical and chemical properties and affected the growth and differentiation of bone marrow-derived cells 6,17,20. Our data further indicate that incorporation of these gel-derived glasses into a HA matrix enhanced growth and osteogenic differentiation of human mesenchymal stem cells (MSC) 5.…”
Section: Introductionmentioning
confidence: 57%
“…RANKL treatment of RAW 264.7 cells, plated on bone slices, bone-mimetics or glass slides, leads to osteoclast formation [23], [24], [25], [26], [27]. Two traditional assays used to test for osteoclast presence are the tartarate resistant acid phosphatase (TRAP) assay and bone resorption assays [7].…”
Section: Resultsmentioning
confidence: 99%
“…A separate study on 45S5 Bioglass 45S5 discs showed no significant difference on differentiation of human-bone-marrow-derived MSCs compared to those cultured on tissue culture plastic (with or without bone morphogenetic protein 2, BMP-2) [129]. When bone marrow MSCs were cultured on bioactive sol-gel coatings with low silica content (40 mol.% SiO 2 , 54 mol.% CaO, 6 mol.% P 2 O 5 ), the MSCs differentiated into osteoblasts and osteoclasts (with or without BMP-2 added to the culture) [130], which seems an ideal result for bone regeneration (bone production and remodelling). When the cells were cultured on glass coatings of high silica composition (80 mol.% SiO 2 , 54 mol.% CaO, 6 mol.% P 2 O 5 ), the MSCs differentiated into osteoblasts but not osteoclasts.…”
Section: Ionic Dissolution Products and Osteogenesismentioning
confidence: 99%